Development Projects and ICT: A Review of Non‐Technical Aspects. Issue 1 (5th December 2017) - Kemppainen, Jyri; Tedre, Matti; Sutinen, Erkki
Abstract: The role of information and communication technology (ICT) in international development co‐operation (IDC) is tightly linked with international political agenda. Currently, international development co‐operation emphasizes three concepts: sustainable development, international human rights, and millennium development goals . This article presents to IT professionals six non‐technical aspects for improving ICT oriented IDC projects. Firstly, those ICT projects should be aligned with internationally agreed political agenda. Secondly, they should cohere with internationally agreed development goals. Thirdly, their design should recognize the political and legal context of the host country. Fourthly, their design and implementation have to follow donor guidelines derived from commonly agreed good practices of IDC project management and design—even when the contextual design tools of ICT for development (ICT4D) research are of limited use with the structured design approaches of IDC. Fifthly, ICT oriented IDC projects should have appropriate indicators for their formative and summative evaluation. Sixthly, IT professionals should stay up‐to‐date with constantly developing ICT and evolving IDC. The presented non‐technical aspects of IDC projects are derived from the central concepts and consensuses of IDC as well as from an analysis of the relevant literature, and the six aspects are reflected on our fourteen years of field work in IDC projects in the least developed countries of Sub‐Saharan Africa. We argue that IT professionals are more competent for IDC projects when their technical expertise is complemented with the presented aspects.